2023
DOI: 10.1371/journal.pone.0282596
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the structural connectivity of international trade networks along the “Belt and Road”

Abstract: Assessing the trade network connectivity is essential for understanding the trade network structure, optimizing trade development patterns, and improving uneven trade development along the “Belt and Road” (BRI). From the perspective of connectivity, this paper integrates the frontier algorithms in network science and constructs an analytical framework to identify the mesoscale structures, including the community structure, core-periphery structure, and backbone structure embedded in the network, and further ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…Li et al investigated the evolution characteristics of the natural gas trade network along the "Belt and Road" (BRI) by using the network indicators and showed that there is an increasingly significant polarization effect in the BRI LNG trade network, and that the level of market monopoly is increasing [21]. Subsequently, scholars are no longer limited to a single portrayal of the overall LNG trade network, and network analysis methods such as community detection [22,23], core-periphery division [24,25], and link prediction [26] have also been used to explore the topological structure [27], the market competition pattern [28], and the prediction of the potential trade relations [29] of the LNG trade network, to deeply explore the pattern evolution of the trade network. Filimonova et al constructed directed network diagrams of the LNG trade, where the global LNG trade network was divided into six subgroups, with Qatar having the richest potential links [27].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Li et al investigated the evolution characteristics of the natural gas trade network along the "Belt and Road" (BRI) by using the network indicators and showed that there is an increasingly significant polarization effect in the BRI LNG trade network, and that the level of market monopoly is increasing [21]. Subsequently, scholars are no longer limited to a single portrayal of the overall LNG trade network, and network analysis methods such as community detection [22,23], core-periphery division [24,25], and link prediction [26] have also been used to explore the topological structure [27], the market competition pattern [28], and the prediction of the potential trade relations [29] of the LNG trade network, to deeply explore the pattern evolution of the trade network. Filimonova et al constructed directed network diagrams of the LNG trade, where the global LNG trade network was divided into six subgroups, with Qatar having the richest potential links [27].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Китай як основна рушійна сила та ініціатор вважається «центром», який володіє новітніми технологіями та капіталом, та прагне використати переваги для розвитку економічних зв'язків із країнами периферії. Країни периферії мають нижчі економічні показники, потребують розвитку інфраструктури та інвестицій, а потенційна вигода від участі в ініціативі для них -доступ до китайського капіталу та ринків Китаю [Murray, 2022;Chen, Zhang, Tang, Yu, 2023].…”
Section: зосередженість на інституційній економіці та політичній екон...unclassified
“…They observed significant change of trade community and the center of trade gravity. Chen et al assessed the trade network connectivity of international trade networks along the belt and road [31]. They observed the community structure, core-periphery structure, and backbone structure in the trade networks.…”
Section: Introductionmentioning
confidence: 99%